Anxiety and depression in pregnant women amid COVID-19 pandemic - Shrestha, Pravin; Mahato, Vibha; Subedi, Anil; Shrestha, Shipra (Asian Journal of Medical Sciences, 2021)
Background: COVID-19 has become a global pandemic. It has affected the psychological condition of pregnant women. Aims and Objective: This study aims to assess prevalence of depression and anxiety in pregnancy during COVID-19 pandemic. Materials and Methods: The current study was an observational, cross sectional study conducted in the Department of Obstetrics and Gynecology, Manipal Teaching Hospital. Patients were assessed using Nepali version of Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI) for anxiety and depression respectively. Result: There were total of 115 patients in this study. The prevalence of anxiety according to BAI was 39.1%. The prevalence of depression according to BDI was 19%. There was a statistically significant difference in rate of anxiety according to maternal age (p value 0.028). Anxiety was higher in women less than 20 years of age. Anxiety symptoms were more prevalent i.e., 44.6% in third trimester followed by 31.4% in second trimester and 29.4% in first trimester. Symptoms of depression was higher in women more than 35 years of age (27.2%) and in second trimester of pregnancy (27.2%). Conclusion: Antenatal anxiety and depression are important issues because it impacts both maternal wellbeing and fetal health. Prevalence of anxiety and depression among pregnant women during COVID 19 pandemic was studied. The prevalence of anxiety and depression was 39.1% and 19% respectively.